HSP60-Derived Peptide as an LPS/TLR4 Modulator: An in silico Approach - Vila-Casahonda, Rafael Gustavo; Lozano-Aponte, Jorge; Guerrero-Beltrán, Carlos Enrique (Frontiers in Cardiovascular Medicine, 2022)
As a part of innate immunity mechanisms, the Toll-like receptors (TLRs) signaling pathway serves as one of the mainstay lines of defense against pathogenic microorganisms and cell dysfunction. Nevertheless, TLRs overactivation induces a systemic proinflammatory environment compromising organ function or causing the patient’s death. TLRs modulators, especially to TLR4, remain a promising approach for inflammatory diseases treatment, being peptide-based therapy a trendy approach. Heat shock protein 60 (HSP60) not only plays a pivotal role in the development of several maladies with strong inflammatory components; nevertheless, HSP60 peptides possess anti-inflammatory properties in TLR4-mediated diseases, such as diabetes, arthritis, atherosclerosis, to mention some. Experimental treatment using HSP60 peptides has proven to be protective in preclinical models in the setting of the heart by virtue of hampering inflammation and modulating the activity of immune cells. Nonetheless, the effect that these peptides may exert directly on cells that express TLR and its role to inhibit overactivation remains elusive. The aim of this study was to evaluate a 15 amino acid long-HSP60 peptide (Peptide-2) in the lipopolysaccharide (LPS) binding site of TLR4/MD2 by molecular docking and molecular dynamics, finding that most poses were present into the hydrophobic pocket of MD2. This interpretation is supported by the fact that the binding affinities obtained in our model for the antagonist Eritoran, were closely related to those of Peptide-2, which also showed that it does not undergo drastic structural changes, moving in a delimited space, and maintaining the same orientation during the simulation. With our results, we propose the plausibility of this peptidic approach for TLR4 modulation as a promising therapy relevant to the treatment of TLR4-related cardiovascular diseases.